The impact of knowledge management on the quality of services in nursing homes - Kejžar, Anamarija; Dimovski, Vlado; Colnar, Simon (Frontiers in Psychology, 2023)
Current management strategies in nursing homes (NH) aim to ensure effective knowledge management (KM) in order to provide best possible services to residents. Teamwork in NH is essential for effective delivery of the highest quality of services. In our quantitative study, we examined how two Slovenian state NH that adopted the E-Qalin quality management model adapted their KM, and what impact their quality management system and KM activities actually have on the quality of services. Furthermore, we examined how two Slovenian private NH that have not adopted a certified quality management program (like ISO or E-Qalin) tackle the issue of quality of services from the KM perspective. The sample consisted of 80 nursing professionals. In every NH that is part of this study, teamwork is essential and every individual that was involved in our survey is part of a team. In our study, we analyzed relationships between individual variables using linear regression. We found a significant and positive relationship between knowledge creation, transfer, and implementation in NH with and without the E-Qalin certificate. We found a significant and positive relationship between knowledge storage and the quality of services only in NH without a E-Qualin certificate. We also found different teamwork approaches in NH with and without a E-Qalin certificate. Our research results therefore emphasize the need to gain additional insight into quality management and KM in the environment of NH. Our results indicate that the topic of KM in NH is interesting, and it has a positive impact on the quality of services in practice. However, the problem of awareness and knowledge on the topic of KM in the environment of NH still exists, highlighting the need for further research, additional insight, and dissemination of knowledge to every interested stakeholder functioning in the field of NH. The results of the study make an important contribution to the research of KM in NH, focusing on the transfer of tacit knowledge.